Building of soft-hard compound brush in porous PVA/NH2@TAtZnO plural gel and the high-efficiency anti-interference removal on Pb(II). (April 2023) - Liu, Lingli; Xu, Sheng; Wang, Zhenxi; Chen, Xiaoguang; Cao, Meng; Zhang, Shangxi; Liu, Yang; Cui, Jinlong
Abstract: In order to promote the heavy metal ions removal of porous gel adsorbent and protect the adsorbent from other pollutants in wastewater, the tetrapod ZnO whiskers (tZnO) modified by amino-chain brush was introduced into the polyvinyl alcohol (PVA) matrix to prepare the PVA/NH2 @TAtZnO composites with brush structure for toxic Pb(II) removal. The adsorption property, adsorption process and adsorption mechanism were studied by adsorption isotherms, adsorption kinetics, adsorption thermodynamics, SEM-EDS analysis and XPS analysis. And the anti-interference ability and anti-interference mechanism were researched by SEM-EDS analysis and XPS analysis. It was found that the PVA/NH2 @TAtZnO composites displayed a soft-hard compound pore-brush structure and showed a good selective adsorption on Pb(II). The research of isotherms and kinetics indicated that the adsorption process was fitted well to Langmuir model and pseudo-second-order model, respectively, and the research of thermodynamics revealed the endothermic nature. The adsorption mechanism was inferred as the combination of predominant chemisorption and subsidiary physisorption. Comparing with the neat PVA matrix, the PVA/NH2 @TAtZnO composites displayed a good anti-interference property on Pb(II) adsorption and showed an alleviative clogging pore-canal structure in the wastewater with SiO2 NPs or PAC flocculants. The anti-interference intensity ΔQ and anti-interference factor χ were proposed to reflect the anti-interference ability of this adsorbent which was promoted with the increasing amino brush length or density. By the analysis of SEM-EDS and XPS, the anti-interference mechanism was explored as the steric-hinerance effect of tZnO hard brush to suspended SiO2 NPs pollutant and the coordination effect of functional amino soft brush to soluble PAC pollutant. Besides, the prepared PVA/NH2 @TAtZnO adsorbent possessed a good reusability under multiple adsorption-desorption processes and also presented a well applicability in real water matrix. The research indicated the huge potential of prepared PVA/NH2 @TAtZnO adsorbent in heavy metal ions removal. Graphical abstract: Image 1 Highlights: The tZnO is modified by functional amino-chain to prepare NH2 @TAtZnO whiskers. A soft-hard compound brush structure is built in the pore canal of PVA gel. The brush structure shows excellent anti-interference ability on Pb(II) adsorption. The parameter χ is first proposed to describe the anti-interference effect.